Production of Lambda(+)(c) baryons in proton-proton and lead-lead collisions at root S-NN=5.02 TeV - (:unkn) unknown (ELSEVIER, 2020)
The transverse momentum (P-T) spectra of inclusively produced A c P baryons are measured via the exclusive decay channel Lambda(+)(c) -> pK(-)pi(+) using the CMS detector at the LHC. Spectra are measured as a function of transverse momentum in proton-proton (pp) and lead-lead (PbPb) collisions at a nucleonnucleon center-of-mass energy of 5.02TeV. The measurement is performed within the Lambda(+)(c) rapidity interval vertical bar Y vertical bar < 1 in the p(T) range of 5-20GeV/c in pp and 10-20GeV/c in PbPb collisions. The observed yields of Lambda(+)(c) for p(T) of 10-20 GeV/c suggest a suppression in central PbPb collisions compared to pp collisions scaled by the number of nucleon-nucleon (NN) interactions. The Lambda(+)(c)/D-0 production ratio in pp collisions is compared to theoretical models. In PbPb collisions, this ratio is consistent with the result from pp collisions in their common p-r range. (C) 2020 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Lambda(c) baryons; Nuclear modification factor; Heavy flavor; PB-PB COLLISIONS; J/PSI SUPPRESSION; RAPIDITY